(untitled) (Vietnam Journal of Community Medicine, 2024)
Research objective: Describe the job satisfaction rate of medical staff at medical stations in Vinh city, Nghe An province in 2023 and explore some related factors. Research method: Cross-sectional descriptive study conducted on 113 medical staff working at a medical station in Vinh city, Nghe An province from March to September 2023. The research tool is a set of survey questions that were promulgated by the Ministry of Health in 2015 with adjustments. SPSS 20.0 software was used for analysing the average score, standard deviation, and the chi-square test was used for finding out related factors. Results: The average score and overall satisfaction rate with the working environment were 3.83 ± 0.59 and 77.9%; Regarding direct leadership and colleagues, it was 4.26 ± 0.57 and 94.7%; Regarding internal regulations, salary, benefits are 3.81 ± 0.62 and 80.5%; Regarding work, learning and promotion opportunities are 3.80 ± 0.67 and 80.5%. Overall job satisfaction with the Medical Station was 4.09 ± 0.54 and 90.3%. There is a relationship between job satisfaction and factors such as qualifications and number of on-call sessions. Conclusion: The job satisfaction of medical staff with their work and the medical station is quite high. The heads of the units need to continue to maintain the aspects received good feedback from medical staff.